The Behavioral–Governance Fit Theory: Orchestrating Profitability through Internal Dynamics and Corporate Governance in Palestinian Banks - Alslaibi, Naji; Qawasmeh, Rasha; Daraghma, Zahran; Abdelkarim, Naser; Paz, Veronica (Journal of Cultural Analysis and Social Change, 2026)
The research examines the impact of internal behavioral dimensions such as organizational culture (OC), CEO communication subjectivity (SUB), CEO mindset (IA), and autocratic leadership style (LS) on bank profitability and the moderating influence of corporate governance (CG) on these relationships in the Palestinian banking sector. This study presents and validates the proposal of Behavioral–Governance Fit Theory (BGFT) as a model that posits profitability to be derived from the convergence between behavioral dynamics and governance quality, rather than the integration of the two dimensions separately. Panel regression methodologies were adopted to examine data from Palestinian banks over the period 2020–2024. We quantify profitability with Return on Assets (ROA) as the principal factor and Return on Equity (ROE) as a robustness check. CEO letters' sentiment were extracted by natural language processing (TextBlob), and a composite corporate governance index was constructed by principal component analysis (PCA). Our results reveal negative associations between OC, SUB, and IA and profitability and therefore, such rigidity of organization, emotional disclosure, and inward-mindset undermines performance. By contrast, LS positively predicts profitability. Good directive leadership in an uncertain environment leads to short-term efficiency. Moderation analysis showed that CG significantly reduces the impact of IA and partially offsets effects for SUB, but it does not affect OC and LS. This research gives concrete support for the BGFT, presenting a new outlook on how the internal traits that govern internal behavior interact with profits in emerging or more restricted economies .